Nature of feeding practices among children with cleft lip and palate - A Goyal; A K Jena; M Kaur (Wolters Kluwer Medknow Publications, 2012)
Objective: To find out the nature of feeding practices among children with cleft lip and palate. Materials and Methods: A total of 155 subjects of less than 2 years of age with cleft lip and palate were chosen and divided into three groups according to their chronological age. Group I included 47 subjects (M=35, F=12) who were <6 months old, Group II included 56 subjects (M=36, F=20) aged between 6 months and 1 year, and Group III included 52 subjects (M=28, F=24) of age between 1 and 2 years. Both the parents of the subjects with cleft lip and palate were interviewed and the details of the existing feeding practice were recorded on a standard proforma. Chi-square test was applied to find out any significant difference in the feeding method between males and females. Results: Spoon feeding was found as the most common feeding practice method. Breast feeding was the second most common feeding practice method among Group I subjects, whereas bottle feeding was the second most common feeding practice method among Group II and III subjects. The difference in the feeding practice between male and female subjects in all the three groups was very negligible and statistically not significant. Conclusion: Spoon feeding was found as the most common feeding method practiced by the parents of children with cleft lip and palate.